Impact of Recurrent Glomerulonephritis on Renal Graft Survival - Toledo, K.; Pérez-Sáez, M.J.; Navarro, M.D.; Ortega, R.; Redondo, M.D.; Agüera, M.L.; Rodríguez-Benot, A.; Aljama, P. (Transplantation proceedings, 2011)
Glomerular disease causes graft loss in the intermediate and long term, especially recurrent primary renal disease, negatively impacting graft survival. Thus, it must be considered a differential diagnosis in the evaluation of chronic graft dysfunction. The objectives of our study were to compare the impacts of primary glomerular disease on graft survival and association with interstitial fibrosis/tubular atrophy (IFTA) or transplant glomerulopathy. We examined the influence of the relapse of glomerulonephritis (GN) on renal graft survival in a retrospective study of 1057 patients undergoing renal transplantations between March 1981 and October 2009. Among this group, 128 patients were diagnosed with pretransplant GN by renal biopsy. We examined graft survival on recurrence compared with IFTA and transplant glomerulopathy using Kaplan-Meier analysis. We analyzed a cohort of 128 patients who were diagnosed with pretransplant GN by renal biopsy, including 28.9% (37) of whom were males. The mean age was 42.04 ± 13.82 years. The most frequent type was immunoglobulin A GN (IgAGN; 31.3%), followed by membranoproliferative GN (MPGN; 28.9%), rapidly progressive GN (RPGN; 16.4%), focal-segmental GN (FSGN; 13.3%), membranous GN (9.4%), and minimal change GN; (0.8%). Among the 16 cases (12.5%) of GN recurrence; MPGN was associated most frequently (n = 10, 28.9%), followed by FSGN (n = 4, 23.5%), RPGN (n = 1, 4.8%), and IgAGN (n = 1, 2.5%). We noted that 11.8% of subjects to be positive for hepatitis C virus; while 3.9% were hepatitis B virus(HBV)-positive. We observed no differences in hepatic serology between patients who experienced recurrence (HBV 6.3% vs hepatitis C virus [HCV] 18.8%) compared with IFTA (HBV 3.1% vs HCV 9.4%). Fifty-one patients (39.8%) were biopsied after transplantation due to impaired renal function: there were recurrences of GN in 12.5% (n = 16), IFTA in 25% (n = 32), and transplant glomerulopathy in 2.3% (n = 3) cases. The average graft survival in our cohort was 8.36 ± 0.59 years. The median patient survival among those who experienced a recurrence was 8.36 ± 1.79 years; 7.19 ± 1.01 years in IFTA patients; and 3.31 ± 0.91 years in patients with transplant glomerulopathy (log-rank P = .06). Upon multivariate analysis, recurrence of GN was not an independent predictor of renal loss. MPGN was the type of GN that recurred most frequently followed by FSGN. No differences in graft survival were noted between long-term recurrence of GN and other causes of chronic graft dysfunction. The recurrence of primary disease did not worsen the renal graft prognosis versus other causes of chronic graft dysfunction.